Olympia, Griechenland. Das Leonidaion in Olympia. Die Arbeiten des Jahres 2019 - Mächler, Claudia; Schauer, Christa; Distler, Stefan (e-Forschungsberichte des DAI, 2020)
After the completion of the building survey of the Leonidaion in 2018, this year‘s work concentrated on restoring and studying the finds from the southwestern spandrel between the Doric peristyle and the water basins of the courtyard, excavated in 2018 (eDAI-F 2019-1). This small area had remained untouched during both the excavation periods of the 1870s/80s and the 1950s, thus enabling a study of the ancient strata. As the sondage yielded, on top of a destruction deposit, a group of pottery vessels and lamps, and in a thick sandy layer an impressively tall glass beaker datable to the Flavian period, it provides important evidence for the dating of the Roman reconstruction of the Leonidaion, probably after a (partial) destruction already in the 1st century AD.